Engaging patients, clinicians, and the community in a Clinical Data Research Network: Lessons learned from the CAPriCORN CDRN. Issue 2 (8th January 2019) - Tambor, Ellen; Shalowitz, Madeleine; Harrington, Joseph M.; Hull, Kevin; Watson, Natalie; Sital, Shelly; Al Naber, Jennifer; Miller, Doriane
Abstract: Engaging patients, clinicians, and community members in the development of a research network creates opportunities and challenges beyond engagement in discrete learning activities. This paper describes our experiences establishing and maintaining a stakeholder engagement infrastructure for the Chicago Area Patient‐Centered Outcomes Research Network (CAPriCORN) and highlights important lessons learned over the first 4 years. During this time, the CAPriCORN Patient and Community Advisory Committee (PCAC) appointed patient, clinician, and community representatives to governance and advisory groups throughout the network, developed a process and criteria for patient‐ and clinician‐centered review of research proposals, and evolved from a large, diverse group to a smaller yet still diverse, more actively engaged group with connections to the broader community. Key challenges faced by the PCAC have included determining the optimal size and composition of the group, understanding the complex structure of the network as a whole, coordinating with other network entities and functions, and integrating the patient and community voice into the research review process. Efforts to engage stakeholders in clinical data research networks should anticipate and develop solutions to address these challenges.